SISTEM INFORMASI PENGOLAHAN DATA PERTUMBUHAN EKONOMI DAN KETIMPANGAN DI KABUPATEN KLATEN (TAHUN 2003-2012) MENGGUNAKAN FRAMEWORK CODEIGNITER - Koespradono, Koespradono; Suraya, Suraya; Rachmawati, Yuliana (Jurnal Script, 2013)
ABSTRACTÂ Nowadays, computer and software used are widespread in every life, even in economic field. hence, a system helps government in order to get data and information about the growth an imbalance at Klaten regency is needed. its goals are government can gets information of big object position of imbalance degree in Klaten regency easier and the it gives description of implementation of economic growth and imbalance at klaten regency data processing information system. Due to process of data processing system of economic growth and imbalance at Klaten Regency (period 2003-2012) needs data i.e. income and sum total of citizens a year in every subditricts in Klaten regency from 2003-2012. to build the system, PHP and codeigniter framework are needed as programming language and mysql is needed for process the database. with this system, gvernment in klaten regency can gets information of economic growth and imbalance and also it can gives description of implementation of economic growth and imbalance at klaten regency data processing information system.Â Keywords: economic growth, imbalance, data processingÂ